Aggressive periodontitis with a history of orthodontic treatment - Vivek Vijay Gupta; Srinivas Sulugodu Ramachandra (Wolters Kluwer Medknow Publications, 2019)
This report presents a 29-year-old aggressive periodontitis patient from Morocco with a history of orthodontic treatment. Despite all the first molars showing advanced bone loss, the maxillary anterior teeth did not show any periodontal destruction. The scientific literature rarely reports cases of aggressive periodontitis without involving maxillary anterior teeth. The treatment provided includes extraction of hopeless tooth, removal of overhanging restoration, scaling, root debridement, and regenerative periodontal therapy. The discussion highlights the dilemma during diagnosis of the case as either "iatrogenic periodontitis due to orthodontic treatment" or "localized aggressive periodontitis." The age group of 15-35 years is the common age group for patients' seeking orthodontic treatment and the occurrence of aggressive periodontitis. Sound knowledge of periodontitis and identification of early signs of aggressive periodontitis through meticulous periodontal examination may help in earlier identification and minimalistic treatment. Education regarding periodontitis, especially aggressive periodontitis, is essential among orthodontists and general dentists. This case report aims to discuss the dilemma involved during diagnosis of localized aggressive periodontitis.